123 Small Ruminant Beginning Farmer Training. (1st March 2018) - Whitley, N C; Davies, L; Gaskin, J; Waldrop, T; Connelly, F; Seanima, T; Speir, A; Stephens, M; Tedrow, A; Burke, P; Butcher, S; Sheffield, M; et al.
Abstract: Sustainable agriculture depends on building successful farms that can stay in business. Because of the great interest in production and difficulties faced by goat and sheep producers, beginning farmer training is especially important for those interested in small ruminants. Therefore, Fort Valley State University, University of Georgia Extension, University of Georgia Small Business Development Center, AgSouth Farm Credit, and Georgia Organics developed a program entitled the "Journeyman Farmer Certificate Program" (JFCP) funded by the USDA NIFA Beginning Farmer and Rancher Development Program. The JFCP for small ruminants involves three steps: 1) small farm business planning training (or training through AgAware), 2) small ruminant production training, and 3) an internship or mentorship. The first two steps are classroom components with pre-recorded video presentations by Specialists within and from outside of Georgia and learning activities lead by county Extension staff. The small ruminant sessions cover topics such as breeds and breeding stock selection, nutrition and feeding, pasture management, predator control, lambing and kidding, health and diseases, integrated parasite management, meats, and marketing as well as hands-on training (including FAMACHA© certification). After attending and completing evaluations for the first two steps, participants have the option of applying for the intern/mentor program through which they get experienced producer mentorship on their farm or conduct a paid internship on an established farm. Mentors and host producers are also reimbursed for their time. Counties in five areas of the state hosted the small ruminant JFCP for a total of 90 participants. So far, five participants have completed internships/mentorships and were satisfied with the program and very thankful for the opportunity. Of those responding to surveys in the pilot group, 100% increased their knowledge and at least 81% were satisfied with the overall classroom experience (presenters, activities, information, resources, opportunities, time, teaching level, facilitator assistance, etc.). For the online overall small ruminant evaluation, 94% completed the evaluation with at least a score of 70%. So far, this program has been successful in helping county Extension staff provide beginning level education from Specialists to clientele interested in small ruminant production.